FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PEMERINTAH DAERAH: STUDI META-ANALISIS - Eviniar Nugraheni; Priyo Hari Adi (Media Riset Akuntansi, Auditing & Informasi, 2020)
The purpose of this study is to identify the determinants of local government’s financial performance. This research employsa meta-analysis technique with a sample consisting of 33 articles from academic journals, graduate and undergraduate students’ theses reporting on local government’s financial performances in Indonesia published from 2006 to 2016. The results of the study demonstrate that there are five factors affecting local government’s financial performance, that isthe level of the region’s wealth, the size of the local government, leverage, local tax revenue and audit findings. On the other hand, the dependence level,capital expenditure, and legislative size are not shown to be factors local government’s financial performance.